The role of the novel MyAlgos e-medicine Platform in promoting patient-centered self-care management in patients with atrial fibrillation: The emPOWERD trial. (11th May 2021) - Lazaridis, C; Mouselimis, D; Bakogiannis, C; Tsarouchas, A; Antoniadis, A; Papadopoulos, CE; Tzikas, S; Fragakis, N; Vassilikos, VP
Abstract: Funding Acknowledgements: Type of funding sources: None. Background The emergence of digital health has revolutionized most aspects of healthcare. Meanwhile, atrial fibrillation (AF) remains the most common sustained arrhythmia associated with high morbidity and impaired quality of life. Patient-perceived treatment burden can be further optimized by digital health interventions utilizing smartphone technology.  The MyAlgos platform is an integrated software system designed to enhance the remote management and communication between the patient and the healthcare practitioner. The mobile application encourages patient self-management through educational modules and tools to improve medication adherence. The web-based platform allows the health care practitioner to receive live updates on patient status and design personalized self-care management plans. Purpose   To investigate whether the use of the MyAlgos platform by AF patients is safe and improves the quality of self-care, quality of life (QoL),  and hospitalization rate. Methods We designed a single-center, randomized, controlled, prospective, open-label, pilot study to compare the effect of the use of the full-feature MyAlgos platform version versus a stripped-down control version of the platform on the QoL, medication adherence and hospitalization rate in patients with paroxysmal AF.  The full version of the e-medicine platform includes active patient education, communication with the medical team, medication reminders as well as the full record of clinically significant data such as heart rate and blood pressure. Specialized algorithms monitor patient data and alert physicians for potential AF episodes. The control version only allows the recording of patient's heart rate. Results A total of 80 patients with paroxysmal AF were randomized in a 1:1 ratio to receive either the full or the control version of the MyAlgos Platform. The mean age of all patients, 53 (66%) male, was 58.1 ± 9.1 years. Hypertension and diabetes were present in 47 (59%) and 7 (9%) respectively. At baseline, the majority of patients had AF-related symptoms classified as European Heart Rhythm Association (EHRA) I (45%) or EHRA II (24%), while the mean Atrial Fibrillation Effect on QualiTy-of-Life (AFEQT) score was 70.1 ± 17.0.  Between the two groups, there were no statistically significant differences in the baseline characteristics of the participants. Conclusion: The emPOWERD trial will provide data on the impact of a novel e-medicine platform on the QoL, medication adherence and hospitalizations of patients with paroxysmal AF. We anticipate better outcomes for the subjects receiving the full version of the MyAlgos platform, allowing it to positively affect the further management of paroxysmal AF.